Knowledge and Concepts about Breast Cancer among age groups of Iraq Women at Oncology Teaching Hospital in Baghdad - A. Al-Eessa, Raghad.; M. A. Al-Attar, Wafaa; Al-Wandawi, Nuha (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The main aim of the study is to determine the level of knowledge and concepts about breast cancer among age groups of Iraqi women attending the main breast cancer early detection center in Baghdad.Methodology: This cross-sectional study recruited 320 women attending the main breast cancer early detection center in Baghdad aged between (18–63years) collected on May 2010. The sample was divided into three age groups of the sample. The knowledge and concepts about breast cancer are assessed through answers of participants to a structured questionnaire which include 2 parts: part I- knowledge about breast health behaviors and risk factors of breast cancer and part II- concepts about breast cancer Statistical analysis of data is done by application of (SPSS version 14) program.Results: Results: The results of this study show that there is no significant between knowledge and concepts of breast cancer among three age groups (p value>0.05) except on knowledge about childhood radiation exposure as a risk for breast (p value